2022
DOI: 10.1093/jxb/erac221
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of winter wheat response to variable sowing dates and densities in a high-yielding environment

Abstract: Crop multi-model ensembles (MME) have proven to be effective in increasing the accuracy of simulations in modelling experiments. However, the ability of a MME to capture crop response to changes in sowing dates and densities has not yet been investigated. These management interventions are some of the main levers for adapting cropping systems to climate change. Here, we explore the performance of a MME of 29 wheat crop models to predict the effect of changing sowing dates and rates on yield and yield component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Crop growth models (CGMs) play a pivotal role in simulating crop growth, predicting yield, and assessing the effects of climate change and cultivation practices on yield formation (Dueri et al, 2022; Liu et al, 2019; Tang et al, 2023; Ye et al, 2020). However, CGMs may not adequately predict plant phenotype as consequence of genotype × environment × management (G × E × M) interactions for many key adaptive traits.…”
Section: Introductionmentioning
confidence: 99%
“…Crop growth models (CGMs) play a pivotal role in simulating crop growth, predicting yield, and assessing the effects of climate change and cultivation practices on yield formation (Dueri et al, 2022; Liu et al, 2019; Tang et al, 2023; Ye et al, 2020). However, CGMs may not adequately predict plant phenotype as consequence of genotype × environment × management (G × E × M) interactions for many key adaptive traits.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Neupane et al [5] has indicated that as a result of climate change, many crops may show reduced yields, especially in regions with insufficient precipitation. Dueri et al [6] have confirmed that climate changes can reduce cereal yields, requiring adjustments to agronomic recommendations (e.g., sowing date, sowing density, etc. ), such as those for winter wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Also, grain quality is a complex trait that depends on different other traits, where the contribution of each trait further depends on environmental conditions [26]. To cope with climatic changes, it is necessary to work on genetic improvement and agronomical management adaptation to increase wheat productivity [27].…”
Section: Introductionmentioning
confidence: 99%